A review on the bioleaching of toxic metal(loid)s from contaminated soil: Insight into the mechanism of action and the role of influencing factors - Sarkodie, Emmanuel Konadu; Jiang, Luhua; Li, Kewei; Yang, Jiejie; Guo, Ziwen; Shi, Jiaxin; Deng, Yan; Liu, Hongwei; Jiang, Huidan; Liang, Yili; Yin, Huaqun; Liu, Xueduan (Frontiers in Microbiology, 2022)
The anthropogenic activities in agriculture, industrialization, mining, and metallurgy combined with the natural weathering of rocks, have led to severe contamination of soils by toxic metal(loid)s. In an attempt to remediate these polluted sites, a plethora of conventional approaches such as Solidification/Stabilization (S/S), soil washing, electrokinetic remediation, and chemical oxidation/reduction have been used for the immobilization and removal of toxic metal(loid)s in the soil. However, these conventional methods are associated with certain limitations. These limitations include high operational costs, high energy demands, post-waste disposal difficulties, and secondary pollution. Bioleaching has proven to be a promising alternative to these conventional approaches in removing toxic metal(loid)s from contaminated soil as it is cost-effective, environmentally friendly, and aesthetically pleasing. The bioleaching process is influenced by factors including pH, temperature, oxygen, and carbon dioxide supply, as well as nutrients in the medium. It is crucial to monitor these parameters before and throughout the reaction since a change in any, for instance, pH during the reaction, can alter the microbial activity and, therefore, the rate of metal leaching. However, research on these influencing factors and recent innovations has brought significant progress in bioleaching over the years. This critical review, therefore, presents the current approaches to bioleaching and the mechanisms involved in removing toxic metal(loid)s from contaminated soil. We further examined and discussed the fundamental principles of various influencing factors that necessitate optimization in the bioleaching process. Additionally, the future perspectives on adding omics for bioleaching as an emerging technology are discussed.